The Protective Effect of Cladophora glomerate Algae Ethanolic Extract on Some Biochemical Parameters in Rats Experimental Induced Diabetes - Amal K. Abbas; Lubab G. Ali; Osama, I. Awad; Shaymaa, A. Ezaldeen (Institute of Medico-legal Publications Pvt Ltd, 2021)
The efficacy of alcoholic extract of Cladophora glomerate(Cg) algae in lowering levels of glucose , cholesteroland triglycerides in male rats with diabetes induced with Alloxan and as will as the histopathology of thepancreas was investigated in this report. The results showed that the alcoholic extract of algae reduced ofglucose cholesterol and triglycerides levels significantly and a histological examination of pancreatic tissuerevealed the therapeutic potential of Cladophora glomerate algae in inhibiting alloxan toxicity of alloxan.